The Shikhara of the Shiva Temple (Temple 1) - Temples of India Project Team (Jio Institute, 2024)
The shikhara (superstructure) of the Shiva Temple (Temple 1) in Cluster 1 is deteriorating, with a portion having already collapsed. The remaining part reveals brickwork with the chaitya (dormer window) arch design.